2018
DOI: 10.1186/s13054-018-2177-8
|View full text |Cite
|
Sign up to set email alerts
|

The glucocorticoid receptor and cortisol levels in pediatric septic shock

Abstract: BackgroundThere is controversy around the prescription of adjunct corticosteroids in patients with fluid-refractory septic shock, and studies provide mixed results, showing benefit, no benefit, and harm. Traditional means for evaluating whether a patient receives corticosteroids relied on anecdotal experience or measurement of serum cortisol production following stimulation. We set out to measure both serum cortisol and the intracellular signaling receptor for cortisol, the glucocorticoid receptor (GCR), in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 26 publications
2
29
0
2
Order By: Relevance
“…The GR reduction is in agreement with Jenniskens et al, who reported sepsis-induced organ dysfunction related to a down-regulation of GR in the liver (22). This is in contrast to the ambivalent reports of GR expression in circulating cells (20,21), which may not necessarily represent the role of GR at the organ level during sepsis (35). As reviewed by Cavaillon and Annane (35), in sepsis, organ specific gene expression was determined to share common patterns or show distinctly opposite profiles between different organs (36), whereas circulating cytokines were not reflective of tissue-specific local levels (37).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The GR reduction is in agreement with Jenniskens et al, who reported sepsis-induced organ dysfunction related to a down-regulation of GR in the liver (22). This is in contrast to the ambivalent reports of GR expression in circulating cells (20,21), which may not necessarily represent the role of GR at the organ level during sepsis (35). As reviewed by Cavaillon and Annane (35), in sepsis, organ specific gene expression was determined to share common patterns or show distinctly opposite profiles between different organs (36), whereas circulating cytokines were not reflective of tissue-specific local levels (37).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we have recently demonstrated that impaired GR dimerization aggravated hemodynamic instability and organ dysfunction during LPS-induced circulatory shock (19). Results for GR expression in peripheral blood cells in sepsis are ambivalent (20,21). While a GR down-regulation is associated with organ dysfunction in the septic liver (22), there are no reports of cardiac tissue expression during sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of cortisol has already been associated with poorer sepsis outcomes in human patients. In a study on 164 pediatric patients, Alder et al reported that patients with both low glucocorticoid receptor expression and high serum cortisol had higher rates (75%) of multi-organ (>2) failure and death ( 55 ). Taken together, this evidence suggests that previous EMS and/or PPID diagnosis could be a relevant “predisposition” for horses being treated for sepsis, and outcomes in this patient population may warrant further investigation.…”
Section: Staging Sepsis Modeling Equine Patient Outcomesmentioning
confidence: 99%
“…The a nity of GRs to GC in circulating monocytes is decreased in patients with acquired immunode ciency syndrome [21]. The expression of GR is decreased in critical illness [22], pediatric septic shock, and patients with high serum cortisol [23]. However, hitherto, no study has reported on the GR expression after ROSC in patients who experienced CA.…”
Section: Introductionmentioning
confidence: 99%